An Improved Z-Source Inverter Topology with Fewer Passive Components: Hardware Validation and Modelling - Tyagi, Tushar; Singh, Amit Kumar; Sharma, Himanshu; Khanna, Rintu (Contemporary Mathematics, 2024)
This research investigated a novel Z-source inverter architecture with fewer passive components. The offered inverter has several advantages, including low-frequency switching at 50 Hz, a straightforward modulation technique, and a constant input current. Low switching frequency results in fewer switching losses, which improves the overall efficiency of the inverter. The adoption of a straightforward modulation method allows for more exact control of the output voltage frequency. Because of these qualities, this inverter architecture can be employed in solar applications. This provides a thorough examination of shoot-through and non-shoot-through modes. The comprehensive mathematical underpinning of various modes is described here, and the established mathematical equations are shown to be consistent with the simulation. The number of components, which is only four in number, switching frequency, and boost factor of the presented topology prototype are compared to various well-known topologies in the literature. The power density of the inverter is 25% higher than the topology having the fewest number of components as reported till date for a single phase Z-source inverter. Finally, a laboratory prototype is created to corroborate the analysis and validation of the data reported by the MATLAB simulation.